2016
DOI: 10.1186/s40064-015-1659-2
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of land property lawsuits and rainfalls

Abstract: This article using the database of Taiwanese land property lawsuits studies the economic effects of rainfalls on land property lawsuits during the period of Japanese colonial rule (1920–1941). The results obtained from basic ordinary least squares indicate that it shows no significant influences. However, an interesting result is that, when we adopt the approach of two stage least squares and use the variables of temperature and evaporation as the instrument variables of rainfalls, we find that there are highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
294
5
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(321 citation statements)
references
References 12 publications
(17 reference statements)
18
294
5
4
Order By: Relevance
“…One qualitative study of caregivers of seniors with chronic conditions identified both barriers and facilitators of resilience, with caregivers’ sense of control, mastery, and support (or lack thereof) playing a role in both categories [40]. Importantly, many caregivers report positive changes or growth due to caregiving, even while reporting high levels of burden [13].…”
Section: Discussionmentioning
confidence: 99%
“…One qualitative study of caregivers of seniors with chronic conditions identified both barriers and facilitators of resilience, with caregivers’ sense of control, mastery, and support (or lack thereof) playing a role in both categories [40]. Importantly, many caregivers report positive changes or growth due to caregiving, even while reporting high levels of burden [13].…”
Section: Discussionmentioning
confidence: 99%
“…(2009), Song et al. (2010), Jung (2010), Fan et al (2016) and so on. And their researches mainly contain the maximal monotone operators in Hilbert spaces and the m -accretive operators in Banach spaces.…”
Section: Introductionmentioning
confidence: 99%
“…They are all stigmatized and often feel excluded from the normative “healthy majority” of “common people” (see e.g., Barroso et al, 2014; Liu et al, 2016; Zäske & Gaebel, 2015), sometimes even as iatrogenic effects of public health communication interventions (Guttman & Salmon, 2004). It is moreover worth mentioning that not only the manifestly ill face blame, guilt, and stigmatization.…”
Section: Introductionmentioning
confidence: 99%